2003
DOI: 10.1007/s00421-003-0882-7
|View full text |Cite
|
Sign up to set email alerts
|

The optimal locomotion on gradients: walking, running or cycling?

Abstract: On level ground, cycling is more economical than running, which in turn is more economical than walking in the high speed range. This paper investigates whether this ranking still holds when moving on a gradient, where the three modes are expected to be mainly facing the same burden, i.e. to counter gravity. By using data from the literature we have built a theoretical framework to predict the optimal mode as a function of the gradient. Cycling was found to be the mode of choice only below 10-15% gradient, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 13 publications
(16 reference statements)
2
39
0
Order By: Relevance
“…2) and about 1.0 m s À1 for C net (Fig. 4); these values are identical or close to values found during unloaded walking in other studies (Ardigo et al 2003;Bobbert 1960;Cotes and Meade 1960;DeJaeger et al 2001;di Prampero 1986;Zarrugh et al 1974). The difference between the two optimal speeds can be explained by looking at how they are calculated.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…2) and about 1.0 m s À1 for C net (Fig. 4); these values are identical or close to values found during unloaded walking in other studies (Ardigo et al 2003;Bobbert 1960;Cotes and Meade 1960;DeJaeger et al 2001;di Prampero 1986;Zarrugh et al 1974). The difference between the two optimal speeds can be explained by looking at how they are calculated.…”
Section: Discussionsupporting
confidence: 75%
“…However, previous studies have shown that: (1) for a given unloaded walking speed, the metabolic rate increases exponentially with increasing positive gradient (Ardigo et al 2003;Bobbert 1960;Margaria 1938); and (2) the energy expenditure per unit of total mass is a constant for a given positive gradient and speed (Goldman and Iampetro 1962). Thus, in uphill walking, the optimal speed should be the same with or without a load, but should decrease with increasing positive gradient.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could be related to relatively smaller percent differences of ventilation between normoxia and hypoxia during walking on the level slope at faster walking speeds (S1 Fig and S1 Table). An upward shift of the U-shaped CoT curve had been reported when walking on the uphill slope [7,13,33,42], pregnant or obese [32,43], or aged [44,45] only at normoxia. Horiuchi et al [14] recently reported that a significantly slower ES was observed when FiO 2 was 11%.…”
Section: Discussionmentioning
confidence: 99%
“…The term a in Equation 1 is a constant pertaining to the production of heat by metabolism and work. Normally a is assumed to equal 2 for walking and 4 for running [11]. The term Ta in Equation 2 is ambient temperature in degrees centigrade.…”
Section: Introductionmentioning
confidence: 99%